Memphis : a novel - Stringfellow, Tara M. (The Dial Press, 2022)
"In the summer of 1995, ten-year-old Joan, her mother, and her younger sister flee her father's violence to the only place they have left: her mother's ancestral home in Memphis. Half a century ago, Joan's grandfather built this majestic house for her grandmother--only to be lynched, days after becoming the first Black detective in Memphis, by his all-white police squad. This wasn't the first time violence altered the course of Joan's family's trajectory, and given who lives inside this house now, she knows it won't be the last. When her aunt opens the door, Joan sees the cousin who once brutally assaulted her. Over the next few years, she is determined not just to survive, but to find something to dream for. Longing to become an artist, she pours her rage and grief into sketching portraits of the women in her life--including old Miss Dawn from down the street, who seems to know something about curses"--